Effect of The Lime Concentration and Soaking Time on the Quality of Durian Stone Chips - Nurdin Efendi Siregar; Setyohadi Setyohadi; Mimi Nurminah (Universitas Sumatera Utara, 2015)
This study was conducted to investigate the effect of the lime concentration and soaking time on the quality of durian stone chips. This study used a completely randomized design with two factors, namely and the concentration of the lime (L) : ( 0.5, 2, 3.5, and 5 % ) and soaking time ( P ) : ( 1, 2, 3 and 4 hours ). The parameters analyzed were moisture content, fat content, protein content, ash conten, and the value of organoleptic ( color, taste and texture). The results showed that the concentration of the lime had highly significant effect on water content, fat content, protein content, ash content, color, taste and texture. The soaking time gave highly significant effect on the moisture content, fat content, protein content, ash content, color, taste and texture. The interaction of the two factors had a highly significant effect on the moisture content, fat content, protein content, ash content, color, taste and texture. The lime concentration of 0.5% and four hours soaking produced the best durian stone chips . Keywords : Durian stone chips ,lime, concentration, soaking time